The beast of Nightfall Lodge - Sidor, S. A. (Steven A.) (Angry Robot, 2019)
When Egyptologist Rom Hardy receives a strange letter from his old friend, the bounty-hunting sniper Rex McTroy, he finds himself drawn into a chilling mystery. In the mountains of New Mexico, a bloodthirsty creature is on the loose, leaving a trail of bodies in its wake. Now, a wealthy big game hunter has offered a staggering reward for its capture, and Rom<U+2019>s patron <U+2013> the headstrong and brilliant Evangeline Waterston <U+2013> has signed the team up for the challenge. Awaiting them are blizzards, cold-blooded trappers, remorseless hunters, a mad doctor, wild animals and a monster so fearsome and terrifying, it must be a legend come to life.